Ruang Lingkup dan Aspek-aspek Kebijakari Pembaharuan Hukum Acara Perdata di Indonesia - Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2002)
This written is aimed to give constribution and suggestion in the frame for law of civil reform in Indonesia. As we:know that the civil law procedure which is existing to days apprehensive enough. Although the freedom of Republic of Indonesia have been pro claimed more than 50 years in the last time, turned outIndonesia still apply law of civil procedure made by Dutch Government that wasrelativel outof date so that it has, no social relevance •with social situation and condition governed. The law ofcivil procedure reform, therefore in Indonesia is as conditio sinequanan in the effort ofproducing the lawexactness and the justice. The law of civil procedure existing to day need tobe rediscussed and reformed by the new law of civil, procedure that is visioner and responsive, either philosophic, jurisdic or sociologic views.'